Dibalik Topeng Penyanyi Campursari (Studi Kasus pada Penyanyi Campursari Anjas Gitarani dan Tini Sebloh di Surakarta) - Handoko, Dwi (representamen, 2020)
Abstract                In facing the intense competition in the music world, a number of singers have made various efforts to maintain their existence in the music world. Singers who face intense competition in the music world include Anjas Gitarani and Tini Sebloh. This research method is descriptive qualitative. The results of this study are: 1) Masks are used as a means to create innovation and creativity, not only as a face covering instrument. Anjas and Tini provide an overview of how creativity and innovation can create creativity to maintain their consistency in singing. 2) Anjas and Tini's vocal quality is actually quite ordinary. However, Anjas and Tini highlighted their stage action by wearing masks when performing on stage. 3). The mask is basically a tool that is used as a face cover. Someone wears a mask so that their real face is not visible. Mask is synonymous with the activity of "covering" so that the face of the singer wearing a mask is not visible. It is no different from Anjas and Tini who wear masks in every appearance. "To close" also implies that a singer must be professional. Whatever the condition is sick, tired, or sad, a singer must stay fit, cheer up, and smile in front of the audience so that the audience feels entertained.               Keywords: The Mask, Anjas Gitarani and Tini Sebloh, Innovation, and Creativity